Sedentary Life and Reduced Mastication Impair Spatial Learning and Memory and Differentially Affect Dentate Gyrus Astrocyte Subtypes in the Aged Mice - Siqueira Mendes, Fabíola de Carvalho Chaves de; Paixão, Luisa Taynah Vasconcelos Barbosa; Diniz, Daniel Guerreiro; Anthony, Daniel Clive; Brites, Dora; Diniz, Cristovam Wanderley Picanço; Sosthenes, Marcia Consentino Kronka (Frontiers in Neuroscience, 2021)
To explore the impact of reduced mastication and a sedentary lifestyle on spatial learning and memory in aged mice, as well as on the morphology of astrocytes at the molecular layer of dentate gyrus (MolDG), different masticatory regimens were imposed. Control mice received a pellet-type hard diet, while reduced masticatory activity group received a pellet diet followed by a powdered diet, and the masticatory rehabilitation group received a pellet diet, followed by powder diet and then a pellet again. To mimic sedentary or active lifestyles, mice were housed in impoverished environment of standard cages, or in an enriched environment. The Morris Water Maze test showed that masticatory deprived group, regardless of environment, was not able to learn and remember hidden platform location, but masticatory rehabilitation combined with enriched environment recovered such disabilities. Microscopic three-dimensional reconstructions of 1800 GFAP-immunolabeled astrocytes from external third of the MolDG were generated using a stereological systematic and random sampling approach. Hierarchical cluster analysis allowed the characterization into two main groups of astrocytes with greater and lower morphological complexities, respectively AST1 and AST2. Once compared to the control group subjected to impoverished environment, deprived animals maintained in same environment for 6 months showed remarkable shrinkage of astrocyte branches. However, long-term environmental enrichment (18-month-old) applied to deprived group reversed the shrinkage effect, with significant increase in morphological complexity of AST1 and AST2, when in an impoverished or enriched environment. During housing under enriched environment, complexity of branches of AST1 and AST2 was reduced by powder diet. in young but not in old mice, where it was reversed by pellet diet. The same was not true for mice housed under impoverished environment. Interestingly, we were unable to find any correlation between MWM data and astrocyte morphological changes. Our findings indicate that both young and aged mice subjected to environmental enrichment, and under normal or rehabilitated masticatory activity, preserve spatial learning and memory. Nonetheless, data suggest that impoverished environment and reduced mastication may start in earlier time and synergize to aggravate age-related cognitive decline, however the association with morphological diversity of AST1 and AST2 at MolDG requires further investigation.